2015
DOI: 10.1097/j.pain.0000000000000309
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and sedative effects of perioperative gabapentin in total knee arthroplasty

Abstract: Gabapentin has shown acute postoperative analgesic effects, but the optimal dose and procedure-specific benefits vs harm have not been clarified. In this randomized, double-blind, placebo-controlled dose-finding study, 300 opioid-naive patients scheduled for total knee arthroplasty were randomized (1:1:1) to either gabapentin 1300 mg/d (group A), gabapentin 900 mg/d (group B), or placebo (group C) daily from 2 hours preoperatively to postoperative day 6 in addition to a standardized multimodal analgesic regime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 33 publications
0
45
1
1
Order By: Relevance
“…One study reported an accumulation of undesirable reactions due to the study drug in the intervention groups; lapse of memory function, impaired balance, hypotension, diplopia, sedation, dizziness and fatigue [85]. …”
Section: Resultsmentioning
confidence: 99%
“…One study reported an accumulation of undesirable reactions due to the study drug in the intervention groups; lapse of memory function, impaired balance, hypotension, diplopia, sedation, dizziness and fatigue [85]. …”
Section: Resultsmentioning
confidence: 99%
“…The management of acute postoperative pain, however, is still far from optimal, and TKA is among the most painful surgeries [19, 36]. In this study, we quantitatively assessed the possible correlations between inflammatory cytokines, muscle damage markers and acute postoperative pain, which few studies have reported, in 96 consecutive primary TKA patients.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized, double-blind study, examining the analgesic and sedative effects of perioperative gabapentin, concluded that there was no improvement in pain control upon ambulation after 24 hours in the gabapentin group. They also noted an increase in sedation at 6 hours postoperatively with gabapentin at a dose of 1,300 mg/d relative to placebo 42. In contrast to the previous studies, there are also studies showing benefits to perioperative gabapentinoids.…”
Section: Multimodal Analgesiamentioning
confidence: 91%